Structural Reforms and Development Process in Uzbekistan's Education System (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Education plays a key role in realizing the potential of individuals and sustainable development of society. Since gaining independence in 1991, Uzbekistan has carried out comprehensive reforms to restructure its education system. The basis of these reforms are the “Law on Education” and the “National Program for Human Resources Development”, adopted on August 29, 1997. These documents defined the priority place of education in state policy and identified long-term development strategies. In 2017, 11-year compulsory education was introduced, replacing the previous 9+3 years system. The purpose of this change was to make the educational process more flexible for students and provide more opportunities for transition to higher education. This article analyzes the historical development of the education system in Uzbekistan, its legal infrastructure and reforms carried out in recent years, and reveals the current state and future trends in the development of the system.